Variation in the perioperative care of women undergoing abdominal-based microvascular breast reconstruction in the United Kingdom (The optiFLAPP Study). Issue 1 (January 2019) - ,; Gardiner, Matthew D.; Giblin, Victoria; Highton, David; Jain, Abhilash; Jeevan, Ranjeet; Jhanji, Shaman; Kwasnicki, Richard M.; Mosahebi, Afshin; Martin, Daniel; Sadideen, Hazim; Skillman, Joanna; et al.
Abstract: Introduction: Abdominal-based microvascular breast reconstruction constitutes approximately one-fifth of reconstructions following mastectomy for breast cancer. Enhanced recovery after surgery (ERAS) protocols have been implemented to improve patient care. The aim of this project was to identify variation in the perioperative care of women undergoing microvascular breast reconstruction to inform development of an ERAS protocol. Methods: Surveys were developed for plastic surgeons, anaesthetists and the lead clinician for breast reconstruction at each unit. These assessed most aspects of perioperative care. A team of medical student collaborators was identified. This team created a list of surgeons and anaesthetists in the United Kingdom by unit. REDCap was used to record their responses. Results: Nineteen (19/39, 49%) lead clinicians, 83 (83/134, 62%) plastic surgeons and 71 (71/100, 71%) anaesthetists from units across the UK completed the surveys. Marked variation was identified in the clinician responses when compared with the national and international guidelines. This variation covered many aspects of patient care including antibiotic and fluid prescribing, surgical technique, post-operative care and recording of patient outcomes. Conclusions: The optiFLAPP national practice survey has demonstrated variation in the perioperative care of women undergoing abdominal-based microvascular breast reconstruction. We propose a large prospective audit to assess current protocols and support development of randomised controlled trials.